"All Solid Along The Line": The Reid Newfoundland Strike of 1918 - McInnis, Peter (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1990)
Abstract As the Canadian and international record will testify, the years between 1917-1920 were critically important to workers' aspirations for industrial unionism. An account of the Newfoundland Industrial Workers' Association (NTWA) has largely been passed over in the writing of the Island's labour history. Yet this organization figures prominently in the events which helped to shape the labour-capital relationship during the wartime period. In the Newfoundland context, the effective use of the strike weapon during this period is a telling indicator of the heightened sense of militancy resulting from the temporary convergence of labour organizations around issues relating to the war. Centred in St John's, but exerting an Island-wide presence, the NTWA arose out of a pressing need for Newfoundlanders to address the economic and political exigencies of World War I. This article examines the NTWA in terms of its structure, membership, and mandate for change with specific reference to the major confrontation waged between the NTWA and their principal opponent, the Reid Newfoundland Company in the spring of 1918.